Preliminary Assessment on Primate Diversity and Potential of PrimaTourism Among Local People and Orang Asli Jakun (Aborigines: Proto-Malay) in Tasik Chini Biosphere Reserve, Pahang, Malaysia - Haris, Hidayah; Nurfitri-Ezatie, Yussof; Othman, Nursyuhada; Ramli, Farah Farhana; Sariyati, Nur Hartini; Abdullah-Fauzi, Nurfatiha Akmal Fawwazah; Najmuddin, Mohd Faudzir; Ilham-Norhakim, Mohd Lokman; Abdul-Latiff, Muhammad Abu Bakar (Journal of Sustainable Natural Resources, 2023)
PrimaTourism is a well-known aspect of nature tourism that provides valuable benefits for the primate species conservation. Malaysia, with its rich diversity of more than 25 primate species inhabited in the country, holds significant potential for enhancing primate-based tourism. However, the information on primate species in potential tourism spots like Tasik Chini remains limited, with only a few data on their behaviour and ecology. Additionally, the lack of comprehensive information on the primate species poses challenges in identifying potential PrimaTourism product. Thus, this study aimed to assess primate diversity and explore the perception of PrimaTourism among local people in Tasik Chini. A survey and interview session were conducted over five days in two villages around Tasik Chini (Kampung Gumum and Felda Chini), involving a total of 32 respondents. Most respondents reported the presence of two common primate species in their area: the long-tailed macaque (Macaca fascicularis) and the pig-tailed macaque (Macaca nemestrina). The result suggested a significant majority (81%) of respondents expressed support for the dusky leaf monkey (Trachypithecus obscurus) as an ideal primate species for PrimaTourism in Tasik Chini, citing its attractive coloration and favoring the development of primate-based tourism. Overall, these findings can serve as essential baseline data for implementing primate tourism in the area, engaging the local community to attract tourists to Tasik Chini effectively and eventually serve as a conservation tool for the primate species.